6(4x-8)=18x

Simple and best practice solution for 6(4x-8)=18x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(4x-8)=18x equation:


Simplifying
6(4x + -8) = 18x

Reorder the terms:
6(-8 + 4x) = 18x
(-8 * 6 + 4x * 6) = 18x
(-48 + 24x) = 18x

Solving
-48 + 24x = 18x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-18x' to each side of the equation.
-48 + 24x + -18x = 18x + -18x

Combine like terms: 24x + -18x = 6x
-48 + 6x = 18x + -18x

Combine like terms: 18x + -18x = 0
-48 + 6x = 0

Add '48' to each side of the equation.
-48 + 48 + 6x = 0 + 48

Combine like terms: -48 + 48 = 0
0 + 6x = 0 + 48
6x = 0 + 48

Combine like terms: 0 + 48 = 48
6x = 48

Divide each side by '6'.
x = 8

Simplifying
x = 8

See similar equations:

| 0=x^3+2x^2+x | | y=x^3+2x^2+x | | 5k-20=4-3k | | 21-15k=26 | | 11=-3+2x | | -16k+97=2k-83 | | 3.75=k(0.5) | | 8.4=m(1.2) | | 3n-20/2=11 | | 3n-20/2=20 | | 8.4=(1.2) | | f(3)=-3x+1 | | 4n/7+8=20 | | x+39=9 | | 0.5y=0.73 | | f(-2)=-3(-2)+4 | | -2-42=-44 | | 4(y+5)=7y-7 | | 21-6x=14 | | 3y-3.8=3y-1.8 | | 3v+4v= | | 60x^2+60x-10=55x^2+61x-6 | | 34-4x=3(x+2) | | 5+9-2y=7y+3-2y | | 60+22x=30x | | 5+10=2 | | x+10+x+14=22 | | 3x^2+8x-24x+35= | | -5x-2-6(x+1)=-(2x+7) | | 5timesx=12 | | -0.4285714286h=6 | | 33=9 |

Equations solver categories